2001
DOI: 10.1103/physrevb.63.104503
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of a π Josephson junction and switch in superconductors with spiral magnetic order

Abstract: It is shown that in magnetic superconductors with spiral magnetic order the Josephson current has an additional contribution which depends: (i) on the relative orientation (magnetic phase) θ = θ L − θ R of magnetizations on the left (L) and right (R) banks of the contact, (ii) on the junction helicitycalculated as a function of the superconducting order parameter ∆, the exchange field energy h and the wave vector Q of the spiral magnetic structure. The π-Josephson contact can be realized in such a system in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 17 publications
5
37
0
Order By: Relevance
“…This result also agrees with the corresponding one in Ref. 13. Note once more the crucial role played by the voltage in this system.…”
Section: Josephson Effect Between Two Non-uniform Helimagnetic Susupporting
confidence: 93%
See 2 more Smart Citations
“…This result also agrees with the corresponding one in Ref. 13. Note once more the crucial role played by the voltage in this system.…”
Section: Josephson Effect Between Two Non-uniform Helimagnetic Susupporting
confidence: 93%
“…Previously a similar analysis was undertaken for helimagnetic superconductors with a uniform superconducting order parameter. 13 In the case of vanishing voltage our results reduce essentially to the ones obtained in Ref. 13.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…We will show here that, although the current I c indeed depends on θ in a way similar to that in Ref. [16], the dependence of I c on various parameters is completely different. The point is that the tunnel Hamiltonian method is not applicable to inhomogeneous superconductors and, in particular, to MS s with a spiral magnetization.…”
Section: Introductionsupporting
confidence: 69%
“…This phenomenon is completely due to the triplet pairing since it dominates on this distance. Kulic and Kulic [129] considered two bulk magnetic superconductors with rotating magnetization separated by an insulating layer. They also have found that the sign of the Josephson current can be negative depending on the relative chirality.…”
Section: Triplet Pairingmentioning
confidence: 99%